KONSEP KEBEBASAN BERAGAMA MENURUT UUD TAHUN 1945 SERTA KAITANNYA DENGAN HAM - Febri Handayani (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
The State guarantees freedom of religion for its citizens, and not interfere with the doctrinal aspects of a religious doctrine. In the same time, the state also must always protect all its citizens and enforce security and order for its citizens that. Every time freedom that intentionally or unintentionallY lead to the disruption of public order and safety, then the country including the government must look to restore public order and safety is as it should In other words, religious freedom is a right that implementation must be alightned with the responsibility to uphold basic human oblgations such as maintaining security and public order. Basic Law (Constitution) in 1945 stated that the state guarantees freedom of religion and spattering article 28E to Article 29 paragraph 1). Infact, in Article 28I of tbe 1945 Constitution stated that religious freedom can not be reduced under any circumstances. Conditions were still reinforced in Article 22 of Law Number 39 year 1999 on Human Rights. Every person has freedom of thought, belief, and religion.